2018
DOI: 10.1039/c7sm01518f
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte scaling laws for microgel yielding near jamming

Abstract: Micro-scale hydrogel particles, known as microgels, are used in industry to control the rheology of numerous different products, and are also used in experimental research to study the origins of jamming and glassy behavior in soft-sphere model systems. At the macro-scale, the rheological behaviour of densely packed microgels has been thoroughly characterized; at the particle-scale, careful investigations of jamming, yielding, and glassy-dynamics have been performed through experiment, theory, and simulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 56 publications
9
49
0
Order By: Relevance
“…2g, Supplementary 5). The analysis confirmed that the geometric parameters (particle shape and porosity) dominate the high-strain behaviors 33 of yielding ( in Fig. 2f and 2g) and the soft plateau ( ), important for shaping and injection.…”
Section: Fig 2 In Silico Simulation and Design Of The Epi Biomaterisupporting
confidence: 63%
See 1 more Smart Citation
“…2g, Supplementary 5). The analysis confirmed that the geometric parameters (particle shape and porosity) dominate the high-strain behaviors 33 of yielding ( in Fig. 2f and 2g) and the soft plateau ( ), important for shaping and injection.…”
Section: Fig 2 In Silico Simulation and Design Of The Epi Biomaterisupporting
confidence: 63%
“…3d). As expected for an essentially non-frictional 33 Our next aim was precise mechanical matching to adipose tissue 12,13 , while conserving a pore size greater than 50μm required for vascularization 34,35 . Fig.…”
Section: Synthesis and Mechanical Characterizationmentioning
confidence: 99%
“…The dependence of λ on G ’ indicates that the microgel pack is deformed elastically and not yielded during buckling. However, if microgel creep occurs over the long time-scale associated with the process, we expect the slow rearrangement of the microgels to occur at constant packing density 20 .
Fig. 3Determining the microbeam moduli to predict λ .
…”
Section: Resultsmentioning
confidence: 99%
“…Lightly cross-linked polyacrylamide microgels with 17 mol% methacrylic acid as an ionizable comonomer are prepared 20,42 . A solution of 8% (w/w) acrylamide, 2% (w/w) methacrylic acid, 1% (w/w) poly(ethylene glycol) diacrylate (MW = 700 g mol −1 ), and 0.1% (w/w) azobisisobutyronitrile in ethanol (490 mL) is prepared.…”
Section: Methodsmentioning
confidence: 99%
“…At low shear rates, the shear stress is constant and independent of shear rate, indicating a non-zero yield stress (~1 to 10 Pa) characteristic of a solid material. At higher shear rates, however, the shear stress follows a power law dependence on shear rate, indicating that the solid matrix becomes fluidized-the individual hydrogel particles rearrange with respect to each other and the medium yields (20). This feature enables us to 3D-print populations within the pore space in defined architectures.…”
Section: Methodsmentioning
confidence: 99%